Gestión de obras públicas y responsabilidad social del organismo supervisor de las contrataciones del estado – Iquitos 2023 - Navarro Rosales, Brigitte Roissy (2025)
The present research seeks to establish the relationship that exists between the management of public works and the social responsibility of the State Contracting Supervisory Body-Iquitos, 2023. The basic type methodology, non-experimental design and quantitative level was used, where 50 workers from the State Contracting Supervisory Body were taken as a sample. The findings obtained indicated that, according to the value of 0.040 of the correlation coefficient and 0.782 of significance, it is established that the relationship between public project management and social responsibility is positive, weak and not very significant. Therefore, it depends on the management of public works; If it is effective, so will social responsibility.